2003
DOI: 10.17660/actahortic.2003.604.20
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Pre- And Postharvest Influences on Fruit and Vegetable Quality as Basic Decision for Chain Management

Abstract: For developing a quality chain management of horticultural products radish bulbs and pepino fruits were chosen as model products. In a first attempt the interaction of some of the most important preharvest influences, the climate effect and the ripening stage at harvest, and different postharvest effects, such as packaging, coatings, CA storage were investigated in respect to the product's precondition at harvest. The investigations of radish indicated that the preharvest dependency of quality determining comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…This corresponds to the literature, which show a slightly higher fructose or glucose proportion depending on cultivation period and place [35,[43][44][45]. The sucrose proportion was low with 5 up to 8% in green, purple and Chinese broccoli as well as in purple cauliflower.…”
Section: Sugar Contentssupporting
confidence: 89%
See 2 more Smart Citations
“…This corresponds to the literature, which show a slightly higher fructose or glucose proportion depending on cultivation period and place [35,[43][44][45]. The sucrose proportion was low with 5 up to 8% in green, purple and Chinese broccoli as well as in purple cauliflower.…”
Section: Sugar Contentssupporting
confidence: 89%
“…Rosa et al [8] also observed this phenomenon during a late planting season in Portugal when temperatures were relative low; however, during the summer season when daily mean temperatures were A 20 8C, the contents among the cultivars did not differ in his investigations and were very low. Taking into consideration the data here and those from several other investigations [35], we can conclude that the broccoli cultivar choice can influence the level of health-relevant glucoraphanin content (preliminary step of sulforaphan) when grown between 14 and 18 8C.…”
Section: Glucosinolates Derived From Dihomomethionines or Homomethionsupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, the differences in postharvest glucosinolate metabolism of mini broccoli and mini cauliflower as well as the different responses to altered gas composition of broccoli are assumed to be due to the vegetables' precondition being influenced by the seasonal preharvest conditions and the development stage at harvest as was found for radish (36). The various products' precondition can be demonstrated by variable glucosinolate content at harvest.…”
Section: Resultsmentioning
confidence: 97%